Modeling Heteroscedasticity of Discrete-Time Series in the Face of Excess Kurtosis (Global Journal of Science Frontier Research, 2018)
To tackle the influence of excess kurtosis (which is on the distributions of the innovations, this study considered the presence of outliers in the data on daily closing prices of shares of Skye Bank, January 03, 2006 to November 24, 2016. The data consist of 2690 from the Nigerian Stock Exchange website. Our findings revealed that GARCH(1,1) model normal distribution, EGARCH(1,1) model under normal distribution and EGARCH(1,1) model under student-t distribution fitted adequately to the returns of Skye Bank, Sterling Bank, and Zenith Bank, respectively. However, all the values of 132. 8707, 80.3030, and 26.3794, respectively.
Keywords: heteroscedasticity; outliers; volatility